2013
DOI: 10.1007/s00404-013-2826-8
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of fertility-sparing treatment with megestrol acetate following hysteroscopic curettage for well-differentiated endometrioid carcinoma and atypical hyperplasia in young women

Abstract: Fertility-sparing treatment with MA following entirely hysteroscopic curettage is effective, demonstrating the least toxicity for rigorously selected young women with well-differentiated EC confined to the endometrium or with AH; however, close follow-up is required for the potential consequences of improper patient selection and a substantial rate of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 24 publications
5
28
1
Order By: Relevance
“…Among these 14 studies, 7 only used MPA or MA as FST (3, 7, 15, 1922) and 2 combined GnRH agonist and LNG-IUD (6, 23) whereas 5 used hysteroscopic resection combined to high-dose oral progestin (2, 4, 5, 24, 25). As far as we know, no other study [except Jadoul and Donnez (11)] reported the effect of GnRH agonist combined with hysteroscopic endometrium resection as FST for EIN or EC.…”
Section: Discussionmentioning
confidence: 99%
“…Among these 14 studies, 7 only used MPA or MA as FST (3, 7, 15, 1922) and 2 combined GnRH agonist and LNG-IUD (6, 23) whereas 5 used hysteroscopic resection combined to high-dose oral progestin (2, 4, 5, 24, 25). As far as we know, no other study [except Jadoul and Donnez (11)] reported the effect of GnRH agonist combined with hysteroscopic endometrium resection as FST for EIN or EC.…”
Section: Discussionmentioning
confidence: 99%
“…Sixtyfive patients achieved pathological CR, with a median remission time of 6 months (range 3Y79 months), of which 7 patients experienced recurrence, and the recurrence time ranged from 10 to 24 months. 23,25,28 Just 1 patient 28 was found with ovarian special type cancer; all patients survived with tumor free. There were 26 patients who got pregnant after CR; 4 patients accepted ART, 2 of whom conceived successfully.…”
Section: Information On Hysteroscopic Resection Combined With Progestmentioning
confidence: 98%
“…Retreatment with oral progestins for recurrence after initial complete response continues to be studied. Park et al have shown high complete (re)response rates with both MA and MPA (85 %) as well as 85 % durable complete response (Park et al 2013c Reported pregnancy rates range from 25 % to nearly 73 % (Minig et al 2011;Park et al 2013d;Shan et al 2013). In a large meta-analysis including 559 women, the live birth rate was approximately 28 % (Gallos et al 2012).…”
Section: Risk Of Recurrencementioning
confidence: 94%
“…These small series have all used similar surgical technique: resection of tumor, resection of endometrium adjacent to the tumor, and resection of the myometrium underlying the tumor. If no myometrial invasion was found on final pathology, the women were treated with hormonal therapy (Kalogera et al 2014;Mazzon et al 2010;Shan et al 2013). Some have voiced concerns regarding potential intrauterine adhesions (with repeated instrumentation of the uterine cavity) leading to subsequent infertility; however, these small series have not been able to provide sufficient case numbers to make this assessment.…”
Section: Nonhormonal and Combination Modalitiesmentioning
confidence: 97%
See 1 more Smart Citation